Genotyping of mycobacterium tuberculosis (MTB) using microbead-based spoligotyping and 24-loci miru-vntr to complement tuberculosis prevention and management in Sabah, East Malaysia - Dawn Carmel, Paul (2024)
Sabah, a state in East Malaysia contributes to about 20% of Malaysia’s TB cases with a prevalence of 128/100,000 population compared to the national prevalence of 92/100,000 population. Molecular epidemiology can help guide decisions pertaining to TB prevention and management, but to date information on MTB genotyping is still scant in Sabah. This study aims to determine the circulating MTB diversity in the state and how genotyping could complement existing TB prevention and management efforts. 1060 unique archived MTB clinical isolates from 2015 to 2016, and prospective isolates from 2017 to 2018 from the whole state were randomly selected and matched against the TB patient registration information in the MyTB database. Epidemiological data were obtained from MyTB, MKAKK Laboratory records and SIMKA database. DNA extraction was performed in the MKAKK High Containment TB Laboratory. Spoligotyping and resistotyping were done using the microbead-based TBSPRINT Beamedex assay in UTAR Pathogen Laboratory. SITVIT2, SpolSimilarity Search and SpolLineages Tool were employed to assign MTB spoligopatterns. 1019 isolates were finalised for further analyses from which 102 SITs with 68 existing SITs and 34 newly created SITs (SIT4181 to SIT4215), and 153 orphan spoligopatterns were detected. Eight newly created SITs from an Unknown lineage could be part of an emerging lineage unique to this region. The lineage distributions are: EAI (n=811), Unknown (n=119), T (n=25), Beijing (n=25), LAM (n=17), Manu (n=9), AFRI (n=4), H (n=4), X (n=3), Turkey (n=1), and Atypical (n=1). Duplex 24-loci MIRU-VNTR were performed on selected clustered and unique spoligotyped isolates (N=593) representing Sabah spoligopatterns. 36 isolates were mixed infections. Cluster analysis was done on 556 strains using MIRU-VNTRplus. ETR-B, Mtub2, QUB11b and ETR-A were the most discriminatory loci. Eight clonal complexes and 51 MIT24 profile clusters were discovered. There was no significant correlation between MTB lineages and factors such as age, sex, occupation, nationality and ethnicity. Individual HGDI and clustering rate of spoligotyping and 24-loci MIRU-VNTR were 0.814 and 0.748; and 0.997 and 0.223 respectively. Combination of both spoligotyping and 24-loci MIRU-VNTR rendered an HGDI and clustering rate of 0.998 and 0.223. TB transmission and reactivation rates for conventional contact investigation versus genotyping complemented contact investigation are 6.1% and 93.9% versus 23.6% and 76.4%. Genotyping revealed new possible epidemiological links previously undetected by conventional investigation. Two alternative genotypecomplemented approaches to contact investigation were proposed namely Direct Cluster approach, and Prioritised Cluster approach. Both approaches are yet to be tested in the field. However, the potential of these strategies in terms of deepening the understanding of TB transmission dynamics in addition to cost reduction in TB prevention and management activities could be of interest to the stakeholders. MTB drug-resistance is still relatively low in Sabah. Eighty-four MTB isolates (8.2%) in this study were found to be drug resistant (MDRTB: 6, 0.6%; RRTB: 4, 0.4%; INH-R: 34, 3.3%; and STR-R: 40, 3.9%). The ratio between low level and high level INH resistance (inhA prom mutation:katG mutation) is about 1:1. Five of six MDRTB cases showed the same mutation: rpoB 531_mut_TTG and inhA_prom_mut-15_T suggesting primary drug resistance. Recommendation was made to the Sabah State Health department on the feasibility and the potential impact of genotyping on TB prevention and management activities in the State with the hope to facilitate reduction in TB incidence in Sabah. Whole genome sequencing and universal genotyping were not done due to technical issues. Distribution of samples over the years (2015 to 2018) were not equal due to limited availability of MTB isolates.